2014
DOI: 10.1556/aphysiol.101.2014.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-alcoholic beer on Subjective Sleep Quality in a university stressed population

Abstract: Sleep deprivation affects the homeostasis of the physiological functions in the human organism. Beer is the only beverage that contains hops, a plant which has a sedative effect. Our objective is to determine the improvement of subjective sleep quality using the Pittsburgh Sleep Quality Index (PSQI). The sample was conducted among a population of 30 university students. The study took place during a period of 3 weeks, the first 7 days were used for the Control, and during the following 14 days the students ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…14,15 This has also been suggested in two studies by Franco et al which used non-alcoholic beer as a dietary source of hops over a 2-week period in 30 university students and 17 healthy female nurses, respectively. 33,34 Both these studies reported improvement in night sleep quality (e.g. reduced sleep latency), with the latter study suggesting that the effects on sleep quality were also reflected in decreased self-reported anxiety levels, as measured by the State-Trait Anxiety Inventory.…”
Section: Discussionmentioning
confidence: 93%
“…14,15 This has also been suggested in two studies by Franco et al which used non-alcoholic beer as a dietary source of hops over a 2-week period in 30 university students and 17 healthy female nurses, respectively. 33,34 Both these studies reported improvement in night sleep quality (e.g. reduced sleep latency), with the latter study suggesting that the effects on sleep quality were also reflected in decreased self-reported anxiety levels, as measured by the State-Trait Anxiety Inventory.…”
Section: Discussionmentioning
confidence: 93%
“…The therapeutic potential of alpha acids has been investigated for their wide range of bioactivity against bacteria, osteoporosis, angiogenesis, inflammation and cancer as comprehensively reviewed (Van Cleemput et al, 2009;Karabín et al, 2016). Furthermore, alpha acids were found to exhibit sedative and hypnotic properties (Zanoli et al, 2005;Schiller et al, 2006), indicating their major role in hops' sleeppromoting activity previously reported in animal models (Bravo et al, 1974;Lee et al, 1993;Franco et al, 2012aFranco et al, , 2014 and humans (Vonderheid-Guth et al, 2000;Dimpfel and Suter, 2008;Franco et al, 2012b). This activity is attributed to the positive modulation of γ-aminobutyric acid type A (GABA A ) receptor function demonstrated earlier with hops extracts (Aoshima et al, 2006;Sahin et al, 2016) and alpha acid fractions (Benkherouf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All but one focused on beer. The topics covered have included the impact of non-alcoholic beer on anxiety [ 44 ] and sleep quality [ 45 , 46 ]; the impact of alcohol-free beer enriched with isomaltulose on insulin resistance in diabetic patients with overweight or obesity [ 47 ]; the effect of non-alcoholic beer compared with improved diet and exercise on nutritional status, endothelial function, and quality of life in patients with cirrhosis [ 48 ]; the impact of non-alcoholic beer [ 49 , 50 , 51 ] or alcohol-free wine [ 52 ] on cardiovascular health; and the relationship between non-alcoholic beer and breastfeeding in terms of whether supplementing with non-alcoholic beer improves the oxidative stress and antioxidant content of breast milk [ 53 ] as well as how much ethanol in non-alcoholic beer may reach the breastfed child [ 54 ]. All these studies concluded that the impact of the tested drink was in a favourable direction, but they focused on relatively short-term effects (days to months) and the studies were conducted on small samples (ranging between 7 and 60 participants).…”
Section: Resultsmentioning
confidence: 99%